104k views
3 votes
-5(-4u+6)-6u=6(u-3)-6

User Cxxl
by
4.4k points

2 Answers

3 votes

Answer:

3/4

Explanation:

-5(-4u+6)-6u=6(u-3)-6

20u-30-6u=6u-18-6

14u-30=6u-24

8u-30= -24

8u=6

User Jjramos
by
4.9k points
5 votes

Answer:

u = 3/4

Explanation:

Solve for u:

-5 (6 - 4 u) - 6 u = 6 (u - 3) - 6

-5 (6 - 4 u) = 20 u - 30:

20 u - 30 - 6 u = 6 (u - 3) - 6

Grouping like terms, 20 u - 6 u - 30 = (20 u - 6 u) - 30:

(20 u - 6 u) - 30 = 6 (u - 3) - 6

20 u - 6 u = 14 u:

14 u - 30 = 6 (u - 3) - 6

6 (u - 3) = 6 u - 18:

14 u - 30 = 6 u - 18 - 6

Grouping like terms, 6 u - 18 - 6 = 6 u + (-18 - 6):

14 u - 30 = 6 u + (-18 - 6)

-18 - 6 = -24:

14 u - 30 = 6 u + -24

Subtract 6 u from both sides:

(14 u - 6 u) - 30 = (6 u - 6 u) - 24

14 u - 6 u = 8 u:

8 u - 30 = (6 u - 6 u) - 24

6 u - 6 u = 0:

8 u - 30 = -24

Add 30 to both sides:

8 u + (30 - 30) = 30 - 24

30 - 30 = 0:

8 u = 30 - 24

30 - 24 = 6:

8 u = 6

Divide both sides of 8 u = 6 by 8:

(8 u)/8 = 6/8

8/8 = 1:

u = 6/8

The gcd of 6 and 8 is 2, so 6/8 = (2×3)/(2×4) = 2/2×3/4 = 3/4:

Answer: u = 3/4

User Yuefengz
by
4.7k points